Penggunaan Model PBL Berpendekatan STEM dalam Pembelajaran IPA Fisika Terhadap Kreativitas Peserta Didik - Septi Rosana; Sri Jumini; Firdaus Firdaus (Kappa Journal, 2022)
This research aims to: (1) To find out whether there is an influence on the use of the Problem Based Learning model with STEM (Science, Technology, Engineering, and Mathematics) in learning Physics Science on the creativity of students. (2) To find out how the Problem Based Learning model is adjacent to STEM (Science, Technology, Engineering, and Mathematics) in learning Science physics to the creativity of students. This research belongs to the type of experimental research. This research is a quantitative study that uses a pure experimental method (true experimentation) and uses a pretest-posttest control group design. The research was conducted at SMP Negeri 1 Mojot tengah with samples of class VII C as an experimental class and class VII A as a control class. There are 20 multiple-choice test questions and 20 learning creativity questionnaire items used to collect data. The data analysis technique uses the initial ability similarity test, normality test, homogeneity test, and hypothesis test (two samples t-test).The results showed that: (1) There is an influence on the use of the STEM (Science, Technology, Engineering, and Mathematics) Problem Based Learning model in physics science learning on the creativity of students, this can be seen from the results of the hypothesis test (t-test), namely the tcount = 4,947 and ttable = 1,999. Because tcount > ttable, it has an effect. (2) Problem Based Learning model learning with STEM (Science, Technology, Engineering, and Mathematics) proximity implemented in the experimental class has an influence on the creativity of students. Learning provides examples of activities and problems in everyday life, relates to the subject matter and uses an integrated approach between science, technology, engineering, and mathematics, and finds ways to overcome problems creatively